Prevalence of Sexual Dysfunction in Healthy Women and its Predictors: A Cross-Sectional Study - Sedighe Rezaie-Chamani; Mona Rahnavardi; Shadi Sabetghadam; Sahar Mahbubinejad; Azizeh Farshbaf-Khalili; Nazanin Rezaie (Golestan University of Medical Sciences, 2020)
Background: Sexuality is an important and inseparable part of the life of every woman. Female sexual dysfunction (FSD) has a major influence on quality of life and can lead to personal distress and anxiety. This study aimed to determine the prevalence of sexual dysfunction and predisposing factors in women. Methods: This cross-sectional study was carried out on 400 outpatient women aged 15-49, who had a health record in the health care centers of Rasht, Iran during 2015-2016. Samples were selected through multi-stage cluster sampling method. Data collection tool included demographics and reproductive information, the standard questionnaire of female sexual function index (FSFI). Multivariate linear regression analysis was used to determine the predictors of sexual dysfunction in SPSS 13. Results: The mean±SD score of total FSFI was 28.14±3.82, ranging from 2 to 36. The frequency of sexual dysfunction was 34.3% in total. Multivariate linear regression analysis showed a significant correlation between FSFI and some factors including age, education level, age at menarche, frequency of sex, and knowledge on sexual function. These factors accounted for 12% of the variance in the sexual function index of women. Conclusions: Considering the critical impact of sexual function on the health of couples, paying attention to sexual function in women and its predictors are important to help and plan prevention programs.